Measurement of gross alpha and gross beta activity concentrations in human tooth - Sogut, Omer; Aydin, Mehmet Fatih; Kucukonder, Erdal; Zorer, Ozlem Selcuk; Dogru, Mahmut (Elsevier Sci Ltd, 2010)
The gross alpha and gross beta activity concentrations were measured in human tooth taken from 3 to 6 age-groups to 40 and over ones. Accumulated teeth samples are investigated in two groups as under and above 18 years. The gross alpha and beta radioactivity of human tooth samples was measured by using a gas-flow proportional counter (PIC-MPC 9604-alpha/beta counter). In tooth samples, for female age-groups, the obtained results show that the mean gross alpha and gross beta activity concentrations varied between 0.534-0.203 and 0.010-0.453 Bq g(-1), and the same concentrations for male age-groups varied between 0.009-1.168 and 0.071-0.204 Bq g(-1), respectively. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Gross alpha and beta; Natural radioactivity; Tooth and calcium